DAMPAK PENGGUNAAN LAHAN TERHADAP SUMBER DAYA AIR: STUDI LITERATUR DAN HASIL PENELITIAN - ALWI, LA ODE; MARWAH, SITTI (Jurnal Agroteknos, 2014)
The impacts of land use, from forest to non-forest (mixed garden, husbandry, and fishery), mining, urbanization, industry and infrastructure in upstream area can give negative impact on water resource environment. Its impact in Wanggu watershed during 1992-2010 were: a) increasing of erosion by 17.6 m3 per ha per year (81,9%), sediment by 2.2 m3 per ha per year, b) decreasing of infiltration capacity by 1.8 m per hour, soil permeability by 2.1 cm per hour, base flow and increasing run-off by 262.7 mm per year (48,8%), CRO by 0,13(46,6%), peak discharge (Qmax) by 114.2 m3 per second and decreasing of water available resources (Qmin) by 3.0 m3 per second and ratio Qmax-Qmin by 38.1 and c) decreasing of water quality because of pollution by TSD, nutrient (NO3-, PO4-3, SO4=), DO, BOD, COD, metal (Cu, Fe, Zn), pesticide, pathogen, salt, oil, color and change of temperature regime. Its impact was categorized as light to moderate pollution. The pollution of out-let Wanggu river was classified as serious category by DO, COD and SO4=. The impacts of land use in Batanghari River were: DO, BOD, COD, NH3, NO2, Zn, Fe and Cu with pollution category as light to moderate. Pollution categorized as serious category by waste: agriculture, urbanization, infrastructure and industry occurred in out-let of Ciliwung River Jakarta, and out-let Berantas River in Surabaya city. Decreasing of water volume and water quality also occurred in some states likes in India, Bangladesh, Thailand, Australia, United State of America and Fiji Island. Keywords: Land use impacts, soil conservation, erosion, sedimentation, run-off, water quality